A comparison of repaired, remanufactured and new compressors used in Western Australian small- and medium-sized enterprises in terms of global warming - Biswas, Wahidul; Duong, Victor; Frey, P.; Islam, Mohammad Nazrul (Springer, 2013)
Repaired compressors are compared with remanufactured and new compressors in terms of economic andenvironmental benefits. A detailed life cycle assessment has been carried out for compressors under threemanufacturing strategies: repaired, remanufactured and new equipment. The life cycle assessment of the globalwarming potential of repaired compressors varies from 4.38 to 119 kg carbon dioxide equivalent (CO2-e),depending on the type of components replaced. While greenhouse gas emissions from the remanufacturedcompressors (110 to 168 kg CO2-e) are relatively higher than those from the repaired ones (4.4 to 119 kg CO2-e), anew compressor has been found to produce a larger amount of greenhouse gas emissions (1,590 kg CO2-e)compared to both repaired and remanufactured compressors. Repairing failed compressors has been found to offerend users both dollar and carbon savings in contrast to remanufactured and new compressors. The research alsofound that extended lifetime is more important than the manufacturing processes in terms of greenhouse gasemissions. Since a remanufactured compressor offers a longer life than a repaired compressor, the replacement ofthe latter with the former can avoid 33% to 66% of the greenhouse gas emissions associated with a newcompressor production with a lifetime of 15 to 25 years.